Genomes of Neutrophilic Sulfur-Oxidizing Chemolithoautotrophs Representing 9 Proteobacterial Species From 8 Genera - Watanabe, Tomohiro; Kojima, Hisaya; Umezawa, Kazuhiro; Hori, Chiaki; Takasuka, Taichi E.; Kato, Yukako; Fukui, Manabu (Frontiers in Microbiology, 2019)
Even in the current era of metagenomics, the interpretation of nucleotide sequence data is primarily dependent on knowledge obtained from a limited number of microbes isolated in pure culture. Thus, it is of fundamental importance to expand the variety of strains available in pure culture, to make reliable connections between physiological characteristics and genomic information. In this study, two sulfur oxidizers that potentially represent two novel species were isolated and characterized. They were subjected to whole-genome sequencing together with 7 neutrophilic and chemolithoautotrophic sulfur-oxidizing bacteria. The genes for sulfur oxidation in the obtained genomes were identified and compared with those of isolated sulfur oxidizers in the classes Betaproteobacteria and Gammaproteobacteria. Although the combinations of these genes in the respective genomes are diverse, typical combinations corresponding to three types of core sulfur oxidation pathways were identified. Each pathway involves one of three specific sets of proteins, SoxCD, DsrABEFHCMKJOP and HdrCBAHypHdrCB. All three core pathways contain the SoxXYZAB proteins, and a cytoplasmic sulfite oxidase encoded by soeABC is a conserved component in the core pathways lacking SoxCD. Phylogenetically close organisms share same core sulfur oxidation pathway, but a notable exception was observed in the family Sulfuricellaceae. In this family, some strains have either core pathway involving DsrABEFHCMKJOP or HdrCBAHypHdrCB, while others have both pathways. A proteomics analysis showed that proteins constituting the core pathways were produced at high levels. While hypothesized function of HdrCBAHypHdrCB is similar to that of Dsr system, both sets of proteins were detected with high relative abundances in the proteome of a strain possessing genes for these proteins. In addition to the genes for sulfur oxidation, those for arsenic metabolism were searched for in the sequenced genomes. As a result, two strains belonging to the families Thiobacillaceae and Sterolibacteriaceae were observed to harbor genes encoding ArxAB, a type of arsenite oxidase that has been identified in a limited number of bacteria. These findings were made with the newly obtained genomes, including those from 6 genera from which no genome sequence of an isolated organism was previously available. These genomes will serve as valuable references to interpret nucleotide sequences.